OECD skills outlook 2013 : first results from the survey of adult skills - Organização para a Cooperação e Desenvolvimento Econômico (Paris : OECD Publishing, 2013)
This first OECD Skills Outlook presents the initial results of the Survey of Adult Skills (PIAAC), which evaluates the skills of adults in 22 OECD member countries and two partner countries. The survey was designed to provide insights into the availability of some key skills and how they are used at work and at home through the direct assessment of key information processing skills: literacy, numeracy and problem-solving in technology-rich environments. The book examines the social and economic context, the supply of key information processing skills, who has these skills at what level, the Foreword; Acknowledgements; Table of Contents; Reader's Guide; Executive Summary; Overview; Figure 0.1 Likelihood of positive social and economic outcomes among highly literate adults; Figure 0.2 Literacy proficiency among 16-65 year-olds; Figure 0.3 Literacy skills gap between older and younger generations; Figure 0.4 Distribution of literacy proficiency scores and education in Italy and Japan; Figure 0.5 Correlation between labour productivity and the use of reading skills at work Figure 0.6 Correlation between gender gap in wages and in the use of problem-solving skills at workChapter 1 - The Skills Neededfor the 21st Century; Major trends influencing the development and use of skills; Access to computers and ICTs is widespread and growing; ICTs are changing how services are provided and consumed; Figure 1.1 Access to computers and the Internet at home; Figure 1.2 The growth of e-government; Employment in services and high-skilled occupations is growing; Figure 1.3 Change in the share of employment, by industrial sectors Figure 1.4 Evolution of employment in occupational groups defined by level of educationFigure 1.5 Change in the demand for skills; Figure 1.6 Evolution of employment in occupational groups defined by level of skills proficiency; Figure 1.7 Organisational change and new technologies; Imbalances between the supply of, and demand for, skills in labour marketsare widespread; What the Survey of Adult Skills can tell us; The level of skills proficiency among adults; Which groups in the population have low, medium and high levelsof key information-processing skills The supply of, and demand for, key information-processing and generic skillsin labour marketsHow key information-processing skills are developed and maintained over a lifetime; How key information-processing skills translate into better economicand social outcomes; References and further reading; Chapter 2 - Proficiency in KeyInformation-Processing Skillsamong Working-Age Adults; Box 2.1. A context for cross-national comparisons of proficiency; Figure a GDP per capita, USD; Figure b Population with tertiary education; Figure c Population without upper secondary education Figure d Foreign-born population as a percentage of total populationDefining literacy, numeracy and problem solvingin technology-rich environments; Table 2.1 Summary of assessment domains in the Survey of Adult Skills (PIAAC); Reporting the results; Box 2.2. Relationship between difficulty of assessment items and proficiency of adultson the literacy, numeracy and problem solving in technology-rich environments scales; Proficiency in literacy; Box 2.3. R eading on a screen or on paper: Does it affect proficiency in literacy? Figure a Percentage of respondents taking different pathways in the Survey of Adult Skills (PIAAC) This first OECD Skills Outlook presents the initial results of the Survey of Adult Skills (PIAAC), which evaluates the skills of adults in 22 OECD member countries and two partner countries. The survey was designed to provide insights into the availability of some key skills and how they are used at work and at home through the direct assessment of key information processing skills: literacy, numeracy and problem-solving in technology-rich environments. The book examines the social and economic context, the supply of key information processing skills, who has these skills at what level, the Description based on online resource; title from PDF title page (ebrary, viewed January 18, 2014).